2020
DOI: 10.1186/s12944-020-01248-0
|View full text |Cite
|
Sign up to set email alerts
|

The abnormal lipid profile in obesity and coronary heart disease (CHD) in Pakistani subjects

Abstract: Background: Obesity has become global epidemic in the last three decades, whereas Coronary Heart Disease (CHD) still remains the most important cause of mortality in the world. The study was aimed at determining the pattern of lipid profile for the obese and CHD population in Pakistan. As obesity is a strong predisposing risk factor for CHD, we aimed to analyze the lipid parameters in both conditions and compare them with the healthy controls of the same ethnicity. Methods: Blood samples were collected from on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 38 publications
5
33
0
Order By: Relevance
“…The prevalence of dyslipidemia in adults in China is 34.7% [ 32 ]; it is a strong factor predisposing patients to obesity and CHD [ 5 ]. Elevated levels of TG also appear to be an independent risk factor for CHD [ 17 , 33 ]. The prevalence of dyslipidemia differed significantly among ethnicities ( P = 0.024); the prevalence in Uygur and Kazak groups was significantly higher than in Han, Hui, and Kirgiz groups.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of dyslipidemia in adults in China is 34.7% [ 32 ]; it is a strong factor predisposing patients to obesity and CHD [ 5 ]. Elevated levels of TG also appear to be an independent risk factor for CHD [ 17 , 33 ]. The prevalence of dyslipidemia differed significantly among ethnicities ( P = 0.024); the prevalence in Uygur and Kazak groups was significantly higher than in Han, Hui, and Kirgiz groups.…”
Section: Discussionmentioning
confidence: 99%
“…This disordered lipid metabolism in obese individuals is an important risk factor for type 2 diabetes mellitus 11,12 , but the research on what the key substances are in obese individuals that lead to type 2 diabetes mellitus is still equivocal. Dyslipidemia has been observed to be prevalent in obesity, and this dyslipidemia is usually referred to as hyperlipidemia (hypertriglyceridemia, hypercholesterolemia, hyper-LDL cholesterolemia and hypo-HDL cholesterolemia) 6,23 . A number of studies showed that obesity is accompanied by mixed dyslipidemia, which increases the risk of type 2 diabetes mellitus 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Apparently healthy individuals should get their lipid profiling done once or twice a year and go for appropriate lifestyle changes so as to prevent the onset of metabolic aberrations (39).…”
Section: Discussionmentioning
confidence: 99%